Anaesthesia for awake craniotomy: A retrospective study of 54 cases - Sokhal, Navdeep (Indian J Anaesth, 2015)
BACKGROUND AND AIMS: The anaesthetic challenge of awake craniotomy is to maintain adequate sedation, analgesia, respiratory and haemodynamic stability in an awake patient who should be able to co-operate during intraoperative neurological assessment. The current literature, sharing the experience on awake craniotomy, in Indian context, is minimal. Hence, we carried out a retrospective study with the aim to review and analyse the anaesthetic management and perioperative complications in patients undergoing awake craniotomy, at our centre. METHODS: Medical records of 54 patients who underwent awake craniotomy for intracranial lesions over a period of 10 years were reviewed, retrospectively. Data regarding anaesthetic management, intraoperative complications and post-operative course were recorded. RESULTS: Propofol (81.5%) and dexmedetomidine (18.5%) were the main agents used for providing conscious sedation to facilitate awake craniotomy. Hypertension (16.7%) was the most commonly encountered complication during intraoperative period, followed by seizures (9.3%), desaturation (7.4%), tight brain (7.4%), and shivering (5.6%). The procedure had to be converted to general anaesthesia in one of patients owing to refractory brain bulge. The incidence of respiratory and haemodynamic complications were comparable in the both groups (P > 0.05). There was less incidence of intraoperative seizures in patients who received propofol (P = 0.03). In post-operative period, 20% of patients developed new motor deficit. Mean intensive care unit stay was 2.8 ± 1.9 day (1–14 days) and mean hospital stay was 7.0 ± 5.0 day (3–30 days). CONCLUSIONS: ‘Conscious sedation’ was the technique of choice for awake craniotomy, at our institute. Fentanyl, propofol, and dexmedetomidine were the main agents used for this purpose. Patients receiving propofol had less incidence of intraoperative seizure. Appropriate selection of patients, understanding the procedure of surgery, and judicious use of sedatives or anaesthetic agents are key to the success for awake craniotomy as a procedure.